2020
DOI: 10.1049/iet-epa.2019.0851
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic shielding for bearings discharge currents attenuation: analysis of its effectiveness, losses and impact on the motor performance – a study for design guidelines

Abstract: The authors deal with the use of electrostatic shielding to mitigate the electric discharge machining (EDM) currents on the induction machine bearings. Employing 2D and 3D models, several finite element analysis (FEA) simulations were thoroughly made addressing the shielding effectiveness to attenuate the shaft-to-frame voltage and the associated eddy current losses for different shield widths, thicknesses and materials. The obtained results provide very good guidelines for the practical design of the shieldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The reduction of C wr can also be executed by using an electrostatic shield placed in the space between the stator winding and the rotor. The solutions described in the literature include the cases of shielding winding along the entire length of the stator iron core [22,23] as well as shielding of end-windings [24,25].…”
Section: Methods Based On Changes In the Design Of The Machinementioning
confidence: 99%
“…The reduction of C wr can also be executed by using an electrostatic shield placed in the space between the stator winding and the rotor. The solutions described in the literature include the cases of shielding winding along the entire length of the stator iron core [22,23] as well as shielding of end-windings [24,25].…”
Section: Methods Based On Changes In the Design Of The Machinementioning
confidence: 99%
“…Hence, it cannot capture the unequal sharing of voltage between various turns in one winding coil, resulting in errors in the predictions of common mode current, shaft voltage and bearing current. Furthermore, the end-winding effect is usually neglected in such simplified analytical methods, which can underestimate the winding-rotor capacitance 𝐶 𝑤𝑟 by ~90% as reported in [60].…”
Section: B Analytical Modellingmentioning
confidence: 99%
“…9) was constructed in [67], for the purposes of comparing the 2D and 3D models without end windings. In [60], 3D FEM models were built with end-windings to investigate the electrostatic shielding effects and compare the winding-rotor capacitances of models with and without end-windings. The results showed that the end-windings have significant effects on the winding-to-rotor capacitance, and neglecting their contribution can underestimate the winding-rotor capacitance by 40%-90%.…”
Section: D Finite Element Modellingmentioning
confidence: 99%
“…• Calculation difficulty in the material and geometry. [208][209][210] 4.5.2. Diagnostic of Bearing Currents Faults Inverter-fed IM drives have more potential impact on generating more shaft voltages and subsequently cause bearing current, so their diagnostic is a pre-condition for a prognostic of the overall power system [211].…”
mentioning
confidence: 99%